Bioinductive Collagen Implant Augmentation for Myotendinous Achilles Rupture in a Teenage Competitive Gymnast: A Case Report. Issue 2 (11th April 2023) - Valk, Josiah; Wilk, Michael J.; Murdock, Kelly; Saad, Mohamed A.
Abstract : Case: A 16-year-old female competitive gymnast presented to our orthopaedic clinic with an acute Achilles tendon rupture at the myotendinous junction. Direct end-to-end repair was performed and augmented with a bioinductive collagen patch. The patient had increased tendon thickness at 6 months postoperatively, as well as significant improvements in strength and range of motion at 12 months. Conclusion: Bioinductive collagen patch augmentation of Achilles tendon repair may be a useful adjunct for myotendinous junction Achilles ruptures, particularly in high-demand patients including competitive gymnasts.